2021
DOI: 10.1111/cag.12732
|View full text |Cite
|
Sign up to set email alerts
|

Changes in outdoor physical activities among older people in Sweden: Exploring generational shifts in time spent in natural environments

Abstract: Spending active time in natural environments increases sharply in the years after retirement, the pattern remaining when cohorts move into older phases.• Aside from spatially segregated activities connected with housing situations, no substantial social differences in time spent in natural environments emerge. • There is a need for enabling proximate access to green spaces and publicly available plots for cultivation, challenging ongoing urban densification.We explore to what extent ageing is associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…The majority of patients displayed PA location preferences for being outdoors, in their garden or at home, as well as activity preferences for individual, non-competitive sports. This reflects previous findings which report that retired adults spent more time in outdoor, natural environments, and older adults showed lower preferences for scheduled, competitive or team-based physical activities [ 44 , 45 ]. As our patient sample consisted primarily of older adults, our results could reflect age-related preferences for exercising.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of patients displayed PA location preferences for being outdoors, in their garden or at home, as well as activity preferences for individual, non-competitive sports. This reflects previous findings which report that retired adults spent more time in outdoor, natural environments, and older adults showed lower preferences for scheduled, competitive or team-based physical activities [ 44 , 45 ]. As our patient sample consisted primarily of older adults, our results could reflect age-related preferences for exercising.…”
Section: Discussionsupporting
confidence: 88%
“…Results confirm recent research pointing to the often neglected importance of household work [ 5 , 14 ]. Findings further stress the importance of nature contact and interaction – possibly a cultural feature of Sweden [ 28 ] – as well as everyday walking activity. From a health-promoting perspective, this indicates a need to take account of public health arguments in urban and regional planning, for example, to improve elderly people’s access to green spaces, parks, and gardens and to improve the conditions for walking in urban areas.…”
Section: Discussionmentioning
confidence: 90%
“…As regards housing , people living in single-family houses spent more time active in the natural environment than did people living in apartments, while the opposite held for regular walks in the local neighbourhood. This might reflect differences in access to nature and a compensatory relationship between the two domains of MVPA [ 28 ]. Finally, the observed ten-year period was associated with some major shifts due to cohort changes (i.e., increased car access among upcoming pensioners) and period effects (i.e., the spread of the Internet in society).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, walking is a significant transport mode to allow older people to conduct day-to-day activities, such as shopping, attend meeting places such as community centres, and reach essential services such as healthcare facilities (Garrard, 2013). Vilhelmson and Thulin (2022) and Chatzitheochari and Arber (2011) have also shown that spending active time in outdoor environments increases significantly in retired and older adults.…”
Section: Demographic Characteristics Influencing Outdoor Physical Act...mentioning
confidence: 97%